Analysis of Outage Probability for MC-CDMA Systems Using Different Spread Codes - Deshmukh, Sanjay; Bhosle, Udhav (Asian Journal of Electrical Sciences, 2019)
Modern communication systems demand proper utilisation of bandwidth, high throughput, integration of services and flexibility. To meet these requirements, spread spectrum code-division multiple access (CDMA) techniques have been proposed for various wireless communication systems. Here the individual user is assigned a unique binary code called spreading code used to increase capacity and provide higher robustness to interference. This paper investigates outage probability performance of MIMO multicarrier spread spectrum code-division multiple access (CDMA) with different robust spreading codes namely Walsh-Hadamard (WH), Gold and Kasami codes. Outage probability Poutage is significant performance measure to evaluate the effect of co-channel interference. System’s performance is initially evaluated in terms of outage probability by varying spreading factor (code length L) L= 4, 16, 64,256 for the number of subcarriers (NC) NC =4. In the second case spread factor SF is kept constant at L=64 and Poutage is analysed for varying number of subcarriers NC = 4, 16, 64. Outage probability analysis for system shows that under similar load conditions Kasami spread sequences outperforms Gold codes and WH codes in terms of outage probability for different spreading factor (SF) of codes and for varying number of subcarriers. This is because of its improved peak isolation and low cross-correlation than other.